Seroprevalence of Bordetella pertussis antibodies in mothers and their newborn infants. - Gonik, Bernard (2005)
BACKGROUND: Pertussis is a highly communicable, vaccine-preventable respiratory disease. Although the largest number of reported cases is among young infants, the most rapidly increasing incidence in the USA is in adolescents and young adults. Importantly, adult family members are the likely major reservoir, infecting susceptible infants before completion of childhood vaccination. We studied maternal-neonatal paired blood samples for the presence of pertussis-related antibodies to assess level of immunity and passive transplacental antibody passage. METHODS. Unselected maternal-neonatal cord blood samples were collected from 101 term deliveries in a single urban uninsured/underinsured hospital setting. Sera were analyzed for anti-pertussis toxin (PT), filamentous hemagglutinin (FHA) and pertactin (PRN) IgG antibodies by enzyme-linked immunosorbent assay (ELISA). Antibody titers were calculated using reference line methodology. Antibody values were log-transformed to establish geometric mean titers (GMT) for analysis. Student's t-test, Mann-Whitney, Pearson correlation and chi square were used for statistical comparisons as appropriate. RESULTS. Mean (SD) maternal age, gestational age and birth weight were 26.8 (6.8) years, 38.9 (1.4) weeks and 3239 (501) g, respectively. Detectable maternal levels of anti-PT, FHA and PRN were found in 34.7%, 95.0% and 80.2%, respectively. Maternal GMT (SD) for PT, FHA and PRN were 4.4 (2.6), 26.6 (3.1) and 12.3 (2.9), respectively. There was no significant relationship between PT, FHA or PRN detection or antibody GMT and maternal age. Maternal anti-PT, FHA and PRN were highly correlated with neonatal cord blood values. CONCLUSION: Despite previous childhood immunization, a large number of parous women have low or undetectable pertussis-related antibody levels, suggesting susceptibility to infection. Even with efficient transplacental passage of these antibodies, neonates similarly have limited measurable protection as detected by cord blood sampling. These data support the need for adolescent or adult vaccination against Bordetella pertussis. Healthcare providers and their clients should be aware of the risk for infant infection via family member transmission.